Multiple Transient Extraction Algorithm and Its Application in Bearing Fault Diagnosis - Jie Zhao (IEEE, 2021)
Transient impulsive signal is usually related with the bearing or gear local defect. It is very difficult to extract those multi-transient features due to the non-stationary of the corresponding vibration signals of rotating machinery. Time-frequency analysis is a suitable tool for analyzing non-stationary signals. A multiple transient extracting transform has been proposed in this work, which can not only effectively detect the multiple transient information in the signal, but also achieve a more concentrated time-frequency representation. The results of numerical simulation show the effectiveness of this proposed method. The proposed multi-transient extracting transform can better locate the transient features and has a lower time-consuming and better noise robustness, compared with the traditional time-frequency analysis methods. Finally, multi-transient extraction algorithm is utilized to analyze practical bearing vibration signals. It has been well demonstrated that the proposed method is more effective than other advanced time-frequency methods in the field of transient feature extraction.